Exploring health challenges and coping strategies in young patients undergoing maintenance hemodialysis: a qualitative study - Huiling Rao; Yiqian Guo; Luanning Qiu; Xiaomei Ren (BMC Nephrology)
Abstract Background Maintenance hemodialysis (MHD) presents significant physical, psychological, and social challenges for young patients, affecting their overall well-being and quality of life. There is a lack of qualitative research on the actual experiences and coping mechanisms of young people aged 18 to 45 years undergoing MHD, and understanding how these patients cope with the multidimensional impact of MHD is crucial for developing effective support strategies. This study aimed to explore the physical, mental, and social health challenges faced by young MHD patients and examine the coping strategies they employ to manage these difficulties. Methods A qualitative study was conducted through semi-structured interviews with nine MHD patients in a tertiary hospital located in a new first-tier city in China. The interview data were analyzed using Colaizzi’s method with the aid of NVivo 14 (QSR International) software, and all patients’ information was anonymized to protect their privacy. Results We found that the patients faced physical health problems such as fatigue, dizziness, and dry mouth as their treatments continued. In terms of mental health, depression, irritability, and low self-esteem were reported, as well as adverse reactions that also affected the patients’ mental well-being. The patients also experienced social adjustment problems, such as difficulties with role identity, barriers to employment, and reduced social participation. They reported using many coping strategies, including self-regulation and seeking outside help. Family and partner support also played an important role in the management of the patients’ psychological states. Conclusions This study identified complex and interrelated physical, psychological, and social challenges faced by young MHD patients and explored the coping strategies employed by them to cope with these challenges. By revealing the dynamic interplay between these domains, the findings suggest the development of personalized, multidimensional interventions to improve patient quality of life. The study provides new insights into the real-life experiences of young MHD patients and provides practical recommendations for key stakeholders, including healthcare providers, family members, and policy makers. The authors used AI assistance to draft this abstract, followed by thorough review and revision. Clinical trial number Not applicable.